1999
DOI: 10.1007/s11745-999-0468-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of n−3 and n−6 fatty acids in Atlantic salmon liver: Stimulation by essential fatty acid deficiency

Abstract: Oxidation, esterification, desaturation, and elongation of [1-14C]18:2n-6 and [1-14C]18:3n-3 were studied using hepatocytes from Atlantic salmon (Salmo salar L.) maintained on diets deficient in n-3 and n-6 polyunsaturated fatty acids (PUFA) or supplemented with n-3 PUFA. For both dietary groups, radioactivity from 18:3n-3 was incorporated into lipid fractions two to three times faster than from 18:2n-6, and essential fatty acids (EFA) deficiency doubled the incorporation. Oxidation to CO2 was very low and was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
55
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 37 publications
10
55
2
Order By: Relevance
“…3,6 In a recent dietary trial, the incorporation of 18:2n-6 and 18:3n-3 was increased in hepatocytes from Atlantic salmon (Salmo salar) fed an EFA deficient diet compared to one fed an n-3-supplemented diet. 22 The present study has confirmed this result but also showed that prior supplementation of the cells with DHA did not affect the PUFA uptake and incorporation processes in either cell line. The present study was performed under conditions where neither cell line was metabolically predisposed to storing lipid.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…3,6 In a recent dietary trial, the incorporation of 18:2n-6 and 18:3n-3 was increased in hepatocytes from Atlantic salmon (Salmo salar) fed an EFA deficient diet compared to one fed an n-3-supplemented diet. 22 The present study has confirmed this result but also showed that prior supplementation of the cells with DHA did not affect the PUFA uptake and incorporation processes in either cell line. The present study was performed under conditions where neither cell line was metabolically predisposed to storing lipid.…”
Section: Discussionsupporting
confidence: 85%
“…36 To our knowledge the effects of EFA deficiency on retroconversion processes in cell cultures has not been reported previously, but retroconversion of DHA to EPA and 22:5n-3 was reported to be increased in hepatocytes prepared from salmon fed an EFA deficient diet in comparison with hepatocytes from salmon fed an n-3PUFA supplemented diet. 22 Prior supplementation with DHA also very significantly reduced the page 17 desaturation/elongation of [1- 14 C]18:3n-3 to tetraene and pentaene products in both cell lines.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The linearly increased relative contents of 18:2n−6 and 18:3n−3, and the logarithmic increased relative content of LC-PUFA observed in the present study may indicate that LC-PUFA biosynthesis in gibel carp decreases as dietary lipid concentrations increase. It has been demonstrated that the rates of conversion of 18:2n−6 and 18:3n−3 to LC-PUFA were enhanced by EFA deficiency, and the LC-PUFA supply in the diet potentially impairs the LC-PUFA synthesis pathway in vivo in some species (Ruyter and Thomassen, 1999;Sargent et al, 2002). When the same lipid source was used in the present study, the diets with higher lipid concentrations allowed the fish to receive greater absolute amounts of LC-PUFA, which may inhibit its biosynthesis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The affinity of the desaturation and elongation enzymes for fatty acids is higher for the n-3 series than for the n-6 and n-9 series [6,7]. Only a few studies have simultaneously investigated both the pathways of β-oxidation and desaturation/elongation of fatty acids [8][9][10], and very little has been done regarding the overall metabolic fate of fatty acids in cells. Previous studies on lipid metabolism in salmonids have mainly concentrated on the metabolism of 18:3n-3 [11], and effects of dietary treatment.…”
Section: Introductionmentioning
confidence: 99%